2018
DOI: 10.1016/j.urology.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trend in Incidental Prostate Cancer Detection at Surgery for Benign Prostatic Hyperplasia

Abstract: The increased rate of low-risk PCa detected after BPH surgery in the last decade reflects the clinical practice changes in PCa screening and diagnosis leading to a reduced number of unnecessary biopsies and indolent cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…Prostate-specific antigen (PSA) assessment, digital-rectal examination (DRE), and rebiopsies are performed frequently in order to switch to an invasive treatment when signs of progression appear [7,8]. However, due to the low detection rate of 4-9% of prostate cancer after surgical BPO treatment [9][10][11][12][13], data on oncological outcomes of IPC patients are scarce, especially of those managed with AS.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate-specific antigen (PSA) assessment, digital-rectal examination (DRE), and rebiopsies are performed frequently in order to switch to an invasive treatment when signs of progression appear [7,8]. However, due to the low detection rate of 4-9% of prostate cancer after surgical BPO treatment [9][10][11][12][13], data on oncological outcomes of IPC patients are scarce, especially of those managed with AS.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned pathologic interactions possibly include specific connexions with the low grade and most-likely indolent incidental prostate cancer (iPCa) 62 identified after HoLEP surgery. Thus, they deserve a careful extended follow up on our case-report patient both for BPH/iPCa long-term recovery and schwannomatosis indolent stability, and warrant complementary detailed biochemical and molecular biology analyses, focused primarily on HoLEP and schwannoma FFPE samples, thereby culminating possibly in new developments of the emerging exosomes/ extracellular vesicles-mediated therapeutic/prophylactic armamentarium.…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort, the rise of iPCa rate was postulated to be the results from the changes of clinical practice, and they found that the increasing iPCa rate was accompanied with a decreasing confirmation of benign biopsies prior to the surgeries of obstructive prostatic enlargement. 13 Nevertheless, the sensitivity and specificity of transrectal ultrasound guided-biopsy was around 44% and 73%, 14 respectively. Herein, even though confirming benign tissues from biopsies, urologists would still encounter iPCa.…”
Section: Discussionmentioning
confidence: 99%